2024
DOI: 10.32604/sv.2024.046723
|View full text |Cite
|
Sign up to set email alerts
|

Soundscapes in Arab Cities: A Systematic Review and Research Agenda

Tallal Abdel Karim Bouzir,
Djihed Berkouk,
Theodore S. Eisenman
et al.

Abstract: In the context of Arab cities, this study explores the intricate interplay between cultural, historical, and environmental elements that shape their unique soundscapes. The paper aims to shed light on this underrepresented field of study by employing a three-fold research approach: systematic review, a comprehensive literature review, and the formulation of a future research agenda. The first part of the investigation focuses on research productivity in the Arab world regarding soundscape studies. An analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The methodology of this research was designed based on previous systematic reviews [24,27,30]. This study followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines [31] (see Supplementary Materials).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The methodology of this research was designed based on previous systematic reviews [24,27,30]. This study followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines [31] (see Supplementary Materials).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, despite the significance of this topic, a noticeable absence of literature reviews on this subject within the Arab world has been observed. Based on the authors' knowledge, there has been no published systematic review on noise pollution studies in the Arab world, and only one systematic review paper on soundscape studies was published in 2024 [27]. This lack of scholarly work underscores a considerable gap in academic discussion.…”
Section: Of 24mentioning
confidence: 99%
See 3 more Smart Citations